(untitled) (Fiep Bulletin - online, 2019)
This article presents innovative experiences and experiences developed in the school context, interlaced in aninterdisciplinary perspective involving Physical Education and other curricular components. It was sought to make studentsaware through discussions, lectures, observations, researches and experiences about the importance of changing habits to abetter quality of life in an interdisciplinary way. The methodological bias for the elaboration of this practice was throughinnumerable activities developed as lectures, gymnastics, seminars, practical outdoor activities and among others, working thecontents on Body Mass Index, Healthy Eating and Physical Activity, with the students of Youth and Adult Education, ThemistoclesPinheiro Gadelha Municipal School, located in the eastern part of the city of Manaus / AM. The school was the locus of all thedevelopment of the activities and the teacher was the mediator of the whole process. The coexistence with the students duringthe whole procedure of the actions revealed positive factors regarding the teaching - learning process. It has been realized thatworking with lectures, poster making, group activities, outdoor practical classes and gymnastics is one of the ways for the teacherto develop interesting, relaxed and dynamic classes, aligned with group work and cooperation. Considering that the institution inwhich this work was developed, it needs a careful look at issues involving sedentarism and obesity. For this reason, there is aneed for the teacher to reinvent himself so that the goal of the work can be achieved, appropriating one of the most preciousassets within Education, to creativity.